Limit Equilibrium Method for the Slope Stability Analysis of Coal Mining at PT. Kalimantan Prima Nusantara: Analisis Stabilitas Lereng Tambang Batubara dengan menggunakan Metode Limit Equilibrium pada PT. Kalimantan Prima Nusantara - Andi Al’Faizah Ma’rief; Hedianto Hedianto; Nur Okviyani; Enni Tri Mahyuni; Abdul Affan (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
Various problems on a slope can be influenced by several factors such as slope geometry and also the property value of the slope. The polemic regarding the exhibition conducted on the mining business license of PT. Kalimantan Prima Nusantara which has an area of 1500 hectares. PT. Kalimantan Prima Nusantara, there is a coal mining company located in Kapuas Regency, Central Kalimantan. The slope conditions in the mining area require attention to the stability of the slopes due to the lithological conditions of the research area found types of sedimentary rocks in terms of engineering geology or rock mass weathering class into the rock category. highly weathered – rock that is completely weathered. The purpose of this study is to analyze the mine slopes at GT-01 – GT-02 (South block pit) GT-03 – GT-04 (Central block pit), GT-05 – GT-06 (North block pit). The research used the balance limit method or the Bishop's method to see whether the shear strength on a slope (shear strength) has a high or low safety value. This is based on kinetic analysis by relying on inputs such as cohesion, bulk density, and internal shear angle. The results of this study indicate that the condition of the rock layers on the slopes are dominated by sedimentary materials such as claystone, siltstone and sandstone. The overall slope shows a slope angle of 35°-50 ° and based on the results of the analysis of the condition of the slopes on GT-01 to GT-06 it shows a stable condition with an average factor value of FK =>2.